2019
DOI: 10.3390/w11112240
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Flow Structure around Cylindrical Bridge Piers in Pressure-Flow Conditions

Abstract: The emerging shift of extreme events, combined with an aging infrastructure and bridges, highlights the potential increase in the risk of damage and catastrophic failure of bridges with climate change. This article analyzes the behavior of the flow and turbulence features in proximity to bridge piers, at two different moments of the scour temporal evolution in free-surface and pressure-flow conditions. Bridge pressure-flow conditions occur when the water depth submerges a bridge deck during extreme events. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The comparative study of u v , u w and v w along the pier's mid-plane for the eroded bed experiments was also performed, as illustrated in Bearing in mind that the Reynolds shear stresses are linked to the capacity of the stream to transport sediments and indicate the exchange of turbulent momentum between layers of a stream [44,45], it is understandable that such capacity increases with the developing scour holes, and the region with large value enlarges and moves upstream of the correspondent scour hole.…”
Section: Reynolds Shear Stressesmentioning
confidence: 99%
“…The comparative study of u v , u w and v w along the pier's mid-plane for the eroded bed experiments was also performed, as illustrated in Bearing in mind that the Reynolds shear stresses are linked to the capacity of the stream to transport sediments and indicate the exchange of turbulent momentum between layers of a stream [44,45], it is understandable that such capacity increases with the developing scour holes, and the region with large value enlarges and moves upstream of the correspondent scour hole.…”
Section: Reynolds Shear Stressesmentioning
confidence: 99%
“…Both urbanization and changes in farming practices are part of this demand. Storm surge, hurricane activity, sea level rise, and other natural processes are all associated with an overall increase in the risk of catastrophic occurrences [1][2][3][4]. As a result, many outdated infrastructures, including bridges, were constructed years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Gautam et al [13] used PIV to observe the flow field around a complex array column and found that the average flow velocity and turbulence parameters around the array column were lower than those around a single column. Carnacina [14] studied the average three-dimensional flow velocities, turbulence intensities, Reynolds stress, and turbulent kinetic energy for a cross-section corresponding to the center of the pier using a Nortek acoustic velocimeter. With the progress of computer technology, scholars have started using numerical models to predict the flow structure around piers.…”
Section: Introductionmentioning
confidence: 99%